The postcolonial unconscious - Lazarus, Neil, 1953- (Cambridge ; New York : Cambridge University Press, 2012)
"The Postcolonial Unconscious is a major attempt to reconstruct the whole field of postcolonial studies. In this magisterial and, at times, polemical study, Neil Lazarus argues that the key critical concepts that form the very foundation of the field need to be re-assessed and questioned. Drawing on a vast range of literary sources, Lazarus investigates works and authors from Latin America and the Caribbean, Africa and the Arab world, South, Southeast and East Asia, to reconsider them from a postcolonial perspective. Alongside this, he offers bold new readings of some of the most influential figures in the field: Fredric Jameson, Edward Said and Frantz Fanon. A tour de force of postcolonial studies, this book will set the agenda for the future, probing how the field has come to develop in the directions it has and why and how it can grow further"--
Introduction: the political unconscious of postcolonial studies -- The politics of postcolonial modernism -- Fredric Jameson on 'third-world literature': a defence -- 'A figure glimpsed in a rear-view mirror': the question of representation in 'postcolonial' fiction -- Frantz Fanon after the 'postcolonial prerogative' -- The battle over Edward Said.
Includes bibliographical references (pages 260-289) and index.
ENH
Keywords: Postcolonialism in literature; Postcolonialism and the arts; Literature, Modern -- 20th century -- History and criticism -- Theory, etc; English literature; Developing countries -- Literatures -- History and criticism